Mitochondrial CLPP2 Assists Coordination and Homeostasis of Respiratory Complexes. Issue 1 (22nd June 2020) - Petereit, Jakob; Duncan, Owen; Murcha, Monika W.; Fenske, Ricarda; Cincu, Emilia; Cahn, Jonathan; Pružinská, Adriana; Ivanova, Aneta; Kollipara, Laxmikanth; Wortelkamp, Stefanie; Sickmann, Albert; Lee, Jiwon; et al.
Abstract: Caseinolytic protease contributes to the mitochondrial protein degradation network through supporting coordination and homeostasis of protein complexes encoded across mitochondrial and nuclear genomes. Abstract: Protein homeostasis in eukaryotic organelles and their progenitor prokaryotes is regulated by a series of proteases including the caseinolytic protease (CLPP). CLPP has essential roles in chloroplast biogenesis and maintenance, but the significance of the plant mitochondrial CLPP remains unknown and factors that aid coordination of nuclear- and mitochondrial-encoded subunits for complex assembly in mitochondria await discovery. We generated knockout lines of the single gene for the mitochondrial CLP protease subunit, CLPP2, in Arabidopsis ( Arabidopsis thaliana ). Mutants showed a higher abundance of transcripts from mitochondrial genes encoding oxidative phosphorylation protein complexes, whereas nuclear genes encoding other subunits of the same complexes showed no change in transcript abundance. By contrast, the protein abundance of specific nuclear-encoded subunits in oxidative phosphorylation complexes I and V increased in CLPP2 knockouts, without accumulation of mitochondrial-encoded counterparts in the same complex. Complexes with subunits mainly or entirely encoded in the nucleus were unaffected. Analysis of protein import and function of complex I revealed that while function was retained, protein homeostasis was disrupted, leading to accumulation of soluble subcomplexes of nuclear-encoded subunits. Therefore, CLPP2 contributes to the mitochondrial protein degradation network through supporting coordination and homeostasis of protein complexes encoded across mitochondrial and nuclear genomes.